2016
DOI: 10.1039/c6ra07673d
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine and nicotine in 3% NaCl solution with CO2as corrosion inhibitors for low carbon steel

Abstract: Caffeine and nicotine are excellent corrosion inhibitors under static conditions in low carbon steel immersed in 3% NaCl + CO2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 50 publications
0
20
0
Order By: Relevance
“…In addition, the corrosion inhibition effectiveness of extracellular polymeric substances extracted from waste activated sludge [77] and berberine extracted from Coptis chinensis [67c] was evaluated for CS immersed in CO 2 ‐saturated 3.64 wt.% NaCl solution and for L360 steel immersed in CO 2 ‐saturated 3.5 wt.% NaCl solution, respectively. There were also studies on the corrosion inhibition role of gum arabic, [82] aqueous solutions of caffeine and nicotine, [94] and sophorolipids (a mixture produced by Starmerella bombicola with a carbon source of glucose and rapeseed oil) in CO 2 ‐saturated brine solutions (Table S11 in Supplementary Material). It is important to point out that most of the research studies investigating the use of natural products as CIs in a CO 2 or CO 2 /H 2 S coexisting environment reported significant corrosion protection effectiveness even at significantly low (at a ppm level) concentrations of these natural products.…”
Section: Corrosion Inhibition Of Steel In a Co2 Environmentmentioning
confidence: 99%
“…In addition, the corrosion inhibition effectiveness of extracellular polymeric substances extracted from waste activated sludge [77] and berberine extracted from Coptis chinensis [67c] was evaluated for CS immersed in CO 2 ‐saturated 3.64 wt.% NaCl solution and for L360 steel immersed in CO 2 ‐saturated 3.5 wt.% NaCl solution, respectively. There were also studies on the corrosion inhibition role of gum arabic, [82] aqueous solutions of caffeine and nicotine, [94] and sophorolipids (a mixture produced by Starmerella bombicola with a carbon source of glucose and rapeseed oil) in CO 2 ‐saturated brine solutions (Table S11 in Supplementary Material). It is important to point out that most of the research studies investigating the use of natural products as CIs in a CO 2 or CO 2 /H 2 S coexisting environment reported significant corrosion protection effectiveness even at significantly low (at a ppm level) concentrations of these natural products.…”
Section: Corrosion Inhibition Of Steel In a Co2 Environmentmentioning
confidence: 99%
“…These results clearly illustrated that the passive lm on the sample surface was broken down and the metal suffered serious local corrosion. 51 However, aer addition of WKI, the weight of the samples was not reduced but increased aer 7 d immersion, indicating WKI can promote the passivity of steel rebar and the sample can form a complete protective lm even in the presence of chloride ions. In addition, it can be seen from Table 1 that the differences among the three parallel specimens were very small, indicating that the experimental results are accurate and reliable.…”
Section: Resultsmentioning
confidence: 94%
“…Nicotine adsorbed on metallic surface through physisorption mechanism following the Langmuir adsorption isotherm. The study suggested that nicotine as long time corrosion inhibitor as it showed more than 87% inhibition efficiency after the immersion time of 72 h. In another study [74], inhibition effect of nicotine and caffeine investigated for the corrosion of carbon steel in 3% NaCl solution saturated with CO 2 under static and turbulent conditions. Results showed that caffeine showed better inhibition performance (>90%) as compared to the nicotine (>80%).…”
Section: Pyridine Based Alkaloids As Corrosion Inhibitorsmentioning
confidence: 98%